ANALYSIS OF THE ADDED VALUE OF LIBERIKA COFFEE POWDER IN SAMUSTIDA VILLAGE, TELUK KERAMAT DISTRICT - Wilis Widi Wilujeng; Darmadi Darmadi (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The purpose of the study is to analyze the added value of Liberika coffee powder in Samustida Village, Teluk Keramat District. The Mitra Sejahtera Cooperative in Samustida Village has been processing coffee into coffee powder. Using the Hayami method, the research analysis found that the added value of processing coffee powder was Rp 6,930/kg, with an added value ratio of 39.33%. The coffee powder processing business received a positive added value or was classified as a moderate increase in value. To increase income, production of coffee powder must be increased, and efforts must be made to find raw materials, as well as to utilize the resources available within the cooperative according to their respective roles and functions.